2002
DOI: 10.1093/carcin/23.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cyclooxygenase-2 protein during rat hepatocarcinogenesis caused by a choline-deficient, L-amino acid-defined diet and chemopreventive efficacy of a specific inhibitor, nimesulide

Abstract: Expression of cyclooxygenase (COX)-2 protein during rat hepatocarcinogenesis associated with fatty change, fibrosis, cirrhosis and oxidative DNA damage, caused by a choline-deficient, L-amino acid-defined (CDAA) diet were investigated in F344 male rats, along with the chemopreventive efficacy of the specific COX-2 inhibitor, nimesulide (NIM). Nimesulide, which was administered in the diet at concentrations of 200, 400, 600 and 800 p.p.m. for 12 weeks, decreased the number and size of preneoplastic enzyme-alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 61 publications
4
39
0
Order By: Relevance
“…In order to test this possibility, we monitored the growth rate of MC38 and MC38/HSV-tk tumors in mice treated with the selective COX-2 inhibitor, nimesulide, which has been previously demonstrated to exert antitumor activity. 50,51 In the current study, nimesulide treatment caused a significant inhibition in growth rate of both MC38 and MC38/HSV-tk tumors. However, nimesulide did not decrease the growth rate of MC38/HSV-tk tumors to a level similar to that of nimesulide-treated MC38 tumors (Fig 8).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In order to test this possibility, we monitored the growth rate of MC38 and MC38/HSV-tk tumors in mice treated with the selective COX-2 inhibitor, nimesulide, which has been previously demonstrated to exert antitumor activity. 50,51 In the current study, nimesulide treatment caused a significant inhibition in growth rate of both MC38 and MC38/HSV-tk tumors. However, nimesulide did not decrease the growth rate of MC38/HSV-tk tumors to a level similar to that of nimesulide-treated MC38 tumors (Fig 8).…”
Section: Discussionsupporting
confidence: 48%
“…[46][47][48] Moreover, selective COX-2 inhibitors have been reported to protect from tumorigenesis in vitro and in in vivo cancer models. [49][50][51] These pieces of evidence, as well as the established association of enhanced COX-2 expression with increased tumor growth, suggested that inhibition of PG synthesis would attenuate the enhancement of tumor growth rate that accompanies the presence of the HSV-tk gene. In order to test this possibility, we monitored the growth rate of MC38 and MC38/HSV-tk tumors in mice treated with the selective COX-2 inhibitor, nimesulide, which has been previously demonstrated to exert antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other defects in biochemical pathway include reduced pyruvate oxidation and increased lactic acid production (Lopez-Alarcon and Eboli, 1986;Mazurek et al, 1997;Eigenbrodt et al, 1998;Basso et al, 2004;Wenzel et al, 2005). Reduced fatty acid oxidation (Ockner et al, 1993;Hardy et al, 2003) increased glycerol production (Shaw and Wolfe, 1987;Beck and Tisdale, 2004) modified amino acid metabolism (Peluso et al, 2000;Denda et al, 2002;Maxwell and Rivera, 2003) and increased pentose phosphate pathway activity (Ferretti et al, 1993;Boros et al, 1998Boros et al, , 2000 are some common alterations associated with cancer cells. Mitochondrial mutations were also reported in normal subjects, especially with advancing age.…”
Section: Other Solid Tumorsmentioning
confidence: 99%
“…It specifically inhibits the inducible form of COX, COX-2, rather than the constitutive form, COX-1 (12), and is well tolerated by adult, elderly, and pediatric patients (10). It also has chemopreventive activity against colon, liver, breast, tongue, and urinary bladder carcinogenesis (13)(14)(15)(16)(17) might be used as a radiosensitizer in the treatment of non-small cell lung cancer (18). However, the apoptotic characteristics of the combination of radiation and nimesulide remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%